Activity of trypsin-like enzymes and gelatinases in rats with doxorubicin cardiomyopathy - Iu. А. Gordiienko; Ya. V. Babets; А. О. Kulinich; А. І. Shevtsova; G. О. Ushakova (The Ukrainian Biochemical Journal, 2014)
Activity of trypsin-like enzymes (ATLE) and gelatinases A and B were studied in the blood plasma and extracts from cardiac muscle, cerebral cortex and cerebellum of rats with cardiomyopathy caused by anthracycline antibiotic doxorubicin against the background of preventive application of corvitin and α-ketoglutarate. ATLE significantly increased in blood plasma and extracts from cerebral cortex but decreased in extracts from cardiac muscle and cerebellum in doxorubicin cardiomyopathy (DCMP). In addition, a significant increase of activity of both gelatinases in plasma and tissue extracts was observed. Preventive administration of corvitin and α-ketoglutarate resulted in differently directed changes of activity of the above mentioned enzymes in heart and brain tissues. Obtained data confirm the hypothesis about activation of proteolysis under the influence of anthracycline antibiotics and testify to selective effect of corvitin and α-ketoglutarate on ATLE and gelatinases.